2016
DOI: 10.15376/biores.11.4.9142-9153
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and Fracture Properties of Laminated Bamboo Strips from Gigantochloa scortechinii Polyester Composites

Abstract: The fatigue and fracture properties of bamboo fiber composites made of woven layers were investigated. This study utilized a specific type of bamboo species named Gigantochloa scortechinii (Buluh Semantan). In these experiments, unsaturated polyester (UP) and bamboo fiber (BF) strips were prepared through a hand lay-up technique using 3-mm thick aluminum mould. The composite bamboo strips had a thickness of 1.5 mm. The strips were woven together to make a single layer. The layer was then laminated into several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Hence, the current results suggest that fatigue failure does not occur in Bambusa-Vulgaris Schrad bamboo when the peak stresses are significantly below the critical buckling stress. The above results are consistent with prior reports by Ali et al (Ali et al, 2016), who have also shown that fatigue damage in bamboo is associated with interfacial debonding/cracking, matrix cracking, and fiber buckling/fracture (Figures 9 and 10).…”
Section: Fatigue Behaviorsupporting
confidence: 93%
“…Hence, the current results suggest that fatigue failure does not occur in Bambusa-Vulgaris Schrad bamboo when the peak stresses are significantly below the critical buckling stress. The above results are consistent with prior reports by Ali et al (Ali et al, 2016), who have also shown that fatigue damage in bamboo is associated with interfacial debonding/cracking, matrix cracking, and fiber buckling/fracture (Figures 9 and 10).…”
Section: Fatigue Behaviorsupporting
confidence: 93%
“…The previous research of laminated bamboo composites carried out by Ali et al has been used the buluh semantan bamboo (Gigantochloa scortechinii) with a thickness of 3 mm. It resulted in the best tensile strength of 30 MPa [16]. Another research of HLC using other natural fibers such as Agave sisalana and jute combined with glass fiber is a woven mat (600 gsm) conducted by Ramesh et al [17].…”
Section: Tensile and Flexural Strengthmentioning
confidence: 99%
“…Laminated bamboo boards can also overcome the weaknesses of round bamboo such as limited dimensions and size irregularities between segments [7,8]. Gigantochloa scortechinii bamboo species has been widely used by researchers to produce laminated bamboo boards [9], plywood [10] and polymer bamboo composites [11,12]. Meanwhile, Gigantochloa levis has also been used to produce glued laminated bamboo [13], plywood [14] and bamboo/epoxy composites [15].…”
Section: Introductionmentioning
confidence: 99%